Effect of submucosal injection of platelet-rich plasma on the rate of canine retraction – A split-mouth randomized clinical study - Vinni Arora; Rekha Sharma; Davender Kumar; Gayathri Mohan; Anjali Narwal (Contemporary Clinical Dentistry, 2023)
Introduction: The use of platelet-rich plasma (PRP) has gained popularity in orthodontics in the past decade. PRP is an autologous concentration of platelets rich in growth factors and is hypothesized to play a role in orthodontic tooth movement (OTM) due to its bone remodeling capacity. Objective: The aim of this study was to determine the effect of PRP on the rate of tooth movement in humans. Materials and Methods: Fourteen patients requiring bilateral extraction of upper first premolars were included in the study. PRP (×4) was prepared and injected in the alveolar mucosa, distal to canine on experimental sides. Canine retraction was initiated on the same day of PRP injection using NiTi closed coil springs on both sides. The amount of canine retraction was measured and compared between both sides at the 4th, 8th, 12th, and 16th weeks by measuring the distance between lateral incisor and canine on the cast. Results: Results showed mean displacement of 1.355 mm, 1.232 mm, 1.191 mm, and 1.085 mm on experimental side and 1.265 mm, 1.126 mm, 1.031 mm, and 0.879 mm on control side at the 4th, 8th, 12th, and 16th weeks, respectively. Although increased OTM (13.85% or 1.1 times faster) was observed on experimental side at all time intervals compared to the control group, the result was not statistically significant. Conclusion: 4× concentration of PRP does not accelerate OTM significantly.